2023
DOI: 10.1186/s13148-023-01457-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study in Chinese monozygotic twins identifies DNA methylation loci associated with blood pressure

Abstract: Background Hypertension is a crucial risk factor for developing cardiovascular disease and reducing life expectancy. We aimed to detect DNA methylation (DNAm) variants potentially related to systolic blood pressure (SBP) and diastolic blood pressure (DBP) by conducting epigenome-wide association studies in 60 and 59 Chinese monozygotic twin pairs, respectively. Methods Genome-wide DNA methylation profiling in whole blood of twins was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The primary materials and methods of this study were in accord with those reported in our previously published studies (Wang, Li et al, 2023; Wang, Yao, Li et al, 2023; Wang, Yao, Tan et al, 2023).…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations
“…The primary materials and methods of this study were in accord with those reported in our previously published studies (Wang, Li et al, 2023; Wang, Yao, Li et al, 2023; Wang, Yao, Tan et al, 2023).…”
Section: Methodsmentioning
confidence: 75%
“…All co-twin pairs completed a questionnaire and undertook a health examination after a 10−12 hour overnight fast. The twins’ zygosity was determined by a combination of sex, ABO blood types, and DNA testing (Wang, Yao, Li et al, 2023). The measurement of BMI and BP has been described in our previous studies (Z. Li et al, 2021; Wang, Yao, Li et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These genes exhibit clear and consistent expression in adipose tissue, cardiovascular tissue, and brain tissue (Fig. 3), and are closely associated with both CVD and cancer [50][51][52][53] . The pleiotropy genes that are linked to these risk genes are enriched in various cancer-related pathways as well as cell cycle-related pathways ( gure S13-16).…”
Section: Discussionmentioning
confidence: 96%